Detection of anti-giardia antibodies among selected kelantan cattle farmers:an occupational risk surveillance - Sidi, Wan Nur Izzati Wan Sidi (2020)
Giardiasis, caused by Giardia lamblia, has been recognized as one of the most common intestinal protozoan infections worldwide. As the disease is spread by the faecal-oral route and potentially zoonotic transmitted, occupations such as cattle farmers are one of the high-risk jobs. In Malaysia, the prevalence of giardiasis ranges between 0.2 to 20%, and infection is often associated with malnutrition particularly among children. The reported prevalence inferred only to active cases, but not the people who are exposed to the infection recently. This cross-sectional study was conducted to investigate the prevalence of giardiasis in relation to occupational exposure among cattle farmers in Kelantan and to compare it with other study groups, Orang Asli and blood donor. Achieved serum samples from 90 participants were subjected to an in-house enzyme-linked immunosorbent assay (ELISA) for the detection of anti-Giardia IgG antibody. Sociodemographic data were analysed using SPSS v24.0 (Microsoft Corporation, USA). An in-house ELISA was optimised with standardised parameters as such coating antigen concentration of 10 μg/mL, serum dilution of 1:50, and HRP-conjugated secondary antibody of 1:6000. The seroprevalence of Orang Asli, blood donors, and farmers were 68.7%, 1%, and 27.7% respectively. There were significant (P<0.001) difference between the seroprevalence of Orang Asli and farmers. There were no significant findings shown between subjects’ demographic variables and ELISA OD450nm reading. In conclusion, the seropositivity of giardiasis is higher in the endemic population as compared to the sera of non-endemic population. Further study is required to identify the possible risk factors of the seropositivity.